2011
DOI: 10.1080/13691058.2011.571290
|View full text |Cite
|
Sign up to set email alerts
|

Gender and sexual vulnerability of young women in Africa: experiences of young girls in secondary schools in Uganda

Abstract: Sexuality is part and parcel of students' experiences of schooling manifested in personal friendships, relations and social interaction. These encounters constitute sites within which sexual identities are developed, practiced and actively produced through processes of negotiation. Drawing on qualitative research conducted in 14 selected secondary schools in Central and Western Uganda, the study illuminates gendered sexual vulnerability within patterns of social interaction and young girls gendered experiences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 18 publications
3
64
0
2
Order By: Relevance
“…This is consistent with Mirembe and Davies (2001) and Muhanguzi's (2011) characterisation of gender roles in Uganda, as well as the representation of girls and boys in the PIASCY documents discussed above. Stereotypes of dominant masculinity and vulnerable femininity appear to be reinforced at the school through teachers' informal advice to students outside the classroom as well as the formal curriculum and interactions between girls and boys in the classroom:…”
Section: Attitudes Towards Gender Rolessupporting
confidence: 64%
See 2 more Smart Citations
“…This is consistent with Mirembe and Davies (2001) and Muhanguzi's (2011) characterisation of gender roles in Uganda, as well as the representation of girls and boys in the PIASCY documents discussed above. Stereotypes of dominant masculinity and vulnerable femininity appear to be reinforced at the school through teachers' informal advice to students outside the classroom as well as the formal curriculum and interactions between girls and boys in the classroom:…”
Section: Attitudes Towards Gender Rolessupporting
confidence: 64%
“…The reinforcement of gender stereotypes which portray girls as 'the weaker sex' may be increasing their susceptibility to STIs including HIV, as well as early pregnancies which ensure the loss of their educational opportunities. Mirembe and Davies (2001) and Muhanguzi (2011) have identified aspects of the school environment as a potential risk to young people's SRH in Uganda, including sexual relationships between teachers and students, but given the potential sensitivity of this topic, it was not raised during interviews with teachers in this study. Only one of the participants from outside the school (Mary, Straight Talk representative) referred to transactional relationships between teachers and female students, but this was in a university context.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One survey of .1400 children found that .80% had experienced caning and slapping by teachers. 7 Qualitative studies also highlight that Ugandan girls experience sexual violence and harassment at school but are unable to report it for fear of reprisals, 8 similar to other African settings. 9,10 In this article, we report on the prevalence of physical, sexual, and emotional violence and neglect experienced by children attending primary school, both from school staff members and others, including parents.…”
Section: Resultsmentioning
confidence: 99%
“…Tests administered in groups were silly sentences (which tests reading and cognitive ability, scoring [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], spelling in English (scoring [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], and basic math (scoring 1-40). Global educational performance score relative to peers was computed by adding up the number of times a student scored in the bottom third of the overall distribution for each individual educational test, divided by the number of completed tests.…”
Section: Methodsmentioning
confidence: 99%